Interdelivery Interval and Diabetes Mellitus in a Subsequent Pregnancy - Dude, Annie M.; Battarbee, Ashley; Yee, Lynn M. (American Journal of Perinatology, 2019)
Objective We determined whether time between deliveries is associated with developing diabetes at the time of a subsequent delivery.Study Design This is a case–control study of women who had two consecutive singleton births at the same institution with no pregestational diabetes in the baseline pregnancy. Cases were defined as women who were diagnosed with any type of diabetes at the time of the subsequent delivery. Controls were defined as women who had no diagnosis of diabetes at the time of the subsequent delivery. Interdelivery interval (IDI) was categorized as < 18, 18 to 60, or > 60 months.Results Of 12,263 women, 4.1% (N = 501) were diagnosed with diabetes at the subsequent delivery. Women with diabetes were more likely to have an IDI of >60 months than women without diabetes (9.0 vs. 4.2%, p < 0.001). After controlling for confounding factors, an IDI > 60 months remained associated with development of pregestational or gestational diabetes by the conclusion of the subsequent pregnancy (adjusted odds ratio = 2.13 compared with an IDI of 18–60 months, 95% confidence interval 1.44–3.15).Conclusion A longer IDI is an independent risk factor for the development of diabetes at the time of a subsequent delivery.
Keywords: gestational diabetes; interdelivery interval; pregestational diabetes